The combined effect of alcohol and body mass index on risk of chronic liver disease: A systematic review and meta‐analysis of cohort studies. (22nd December 2020) - Glyn‐Owen, Kate; Böhning, Dankmar; Parkes, Julie; Roderick, Paul; Buchanan, Ryan
Abstract: Background & Aims: Increasingly populations are both overweight/obese and consume alcohol. The risk of liver disease from the combination of these factors is unclear. We performed a systematic review and meta‐analysis to address this important gap in evidence. Protocol registered with PROSPERO(CRD42016046508). Methods: We performed electronic searches of Ovid Medline, Embase Classic + Embase, until 17th June 2020 for cohort studies of adults without pre‐existing liver disease. Primary outcome was morbidity/mortality from chronic liver disease. Exposures were alcohol consumption categorised as within or above UK recommended limits (14 units/112 g per week) and BMI categorised as normal, overweight or obese. Non‐drinkers were excluded. A Poisson regression log‐linear model was used to test for statistical interaction between alcohol and BMI and to conduct a one‐stage meta‐analysis. Results: Searches identified 3129 studies—16 were eligible. Of these, nine cohorts (1, 121, 514 participants) had data available and were included in the analysis. The Poisson model showed no significant statistical interaction between alcohol consumption and BMI on the risk of chronic liver disease. Compared to normal weight participants drinking alcohol within UK recommended limits, relative risk of chronic liver disease in overweight participants drinking above limits was 3.32 (95% CI 2.88 to 3.83) and relative risk in obese participants drinking above limits was 5.39 (95% CI 4.62 to 6.29). Conclusions: This meta‐analysis demonstrated a significantly increased risk of chronic liver disease in participants who were both overweight/obese and consumed alcohol above UK recommended limits. This evidence should inform advice given to patients and risk stratification by healthcare professionals.